Retiform Purpura of the Lower Limbs Associated with Levamisole-Adulterated Cocaine - Stephanie Farrugia; Daniel Micallef; David Pisani; Alexandra Betts; Sandro Vella; Michael J Boffa (European Journal of Case Reports in Internal Medicine, 2022)
A young man was treated in hospital for sepsis, disseminated intravascular coagulation and multi-organ failure. He was a regular intranasal cocaine user up to 1 day prior to symptom onset. Clinical examination revealed extensive retiform purpura affecting both his lower limbs. Skin biopsy revealed widespread thrombosis in the small- and medium-sized vessels of the mid dermis and the subcutaneous fat with surrounding leucocytoclasis. There was also extensive ischaemic necrosis of the upper reticular and papillary dermis and focal ischaemic necrosis of the epidermis. These findings were in keeping with a thrombotic vasculopathy with associated cutaneous ischaemic necrosis, likely associated with levamisole-adulterated cocaine (LAC). An autoimmune screen showed extremely raised levels of anti-B2-glycoprotein IgM, IgG and anti-cardiolipin IgG antibodies, usually seen in antiphospholipid syndrome (APS). The literature describes how APS could be secondary to various underlying conditions, including LAC, and that levamisole toxicity may mimic APS and hence be missed.